JCMAH 2019
DOI: 10.19080/jcmah.2019.09.555776
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Aloe Vera In Treatment: A Literature Review

Abstract: Study researching literature that using aloe vera in treatment or therapy to overcome several health body problems. MethodsSearching article begins of that 10-25 august 2018 by using a search strategy via the CINAHL database, ResearchGate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Other uses include application as an insect repellant and the treatment of diabetes mellitus, antihemorrhoidal agent, gout, tuberculosis, gonorrhea, headaches, and eczema (Barceloux, 2008). Different from traditional treatment modalities, Aloe Vera will great reduce medical cost intended as complementary therapy (Rozani and Kusbaryanto, 2019). Succulent Aloe plants have been used to treat wounds since ancient times and are mentioned in the Ebers papyrus, an important medical text of ancient Egypt, dating from 1550 BCE (Edwards et al, 2015).…”
Section: Aloe Vera Traditional Medicinal Uses In Various Ancient Culturesmentioning
confidence: 99%
See 4 more Smart Citations
“…Other uses include application as an insect repellant and the treatment of diabetes mellitus, antihemorrhoidal agent, gout, tuberculosis, gonorrhea, headaches, and eczema (Barceloux, 2008). Different from traditional treatment modalities, Aloe Vera will great reduce medical cost intended as complementary therapy (Rozani and Kusbaryanto, 2019). Succulent Aloe plants have been used to treat wounds since ancient times and are mentioned in the Ebers papyrus, an important medical text of ancient Egypt, dating from 1550 BCE (Edwards et al, 2015).…”
Section: Aloe Vera Traditional Medicinal Uses In Various Ancient Culturesmentioning
confidence: 99%
“…It identified the effect of Aloe Vera cream 0.5% in chronic anal fissure treatment and it was found that using Aloe Vera cream could reduce pain and accelerate the process of wound healing during chronic anal fissure treatment. It also identified the using of Aloe Vera cream into reduce pain and accelerate the process of post-surgery wound healing, post defection (hemorrhoidectomy) and found that Aloe Vera cream significantly reduced post-surgery pain at 12, 24, 48 hours and 2 weeks post-surgery and patients who is receiving Aloe Vera cream has decreased when take number two significantly at 24 and 48 hours after hemorrhoidectomy and Aloe Vera cream significantly helps wound healing to post surgery patient during 2 weeks (Rozani and Kusbaryanto, 2019). In other clinical studies, topical Aloe Vera was compared to silver sulfadiazine or Vaseline gauze in treating burn wound.…”
Section: Aloe Vera Creammentioning
confidence: 99%
See 3 more Smart Citations